IMPACT OF PERFORMANCE APPRAISAL SYSTEM ON EMPLOYEES PRODUCTIVITY WITH REFERENCE TO HYDERABAD BATTERIES PVT. LTD., HYDERABAD - K. NAGAMANI; P. GIRIJASRI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The working environment of today requires a lot of devotion and work from employees. The time-consuming and vital aspect of a manager's job is performance appraisal. In order to achieve job-related comprehension levels, it entails enhancing performance and fully utilising effectiveness. The distinction between appraiser and appraise is sometimes required in situations where employees must be evaluated by their immediate supervisors. Only the past and the present are considered in assessments. The staff is being evaluated, and they are being urged to improve their efficacy, make use of their skills, overcome their deficiencies, and assess whether their potential and aspirations line up. It should be carried out through thorough tracking of employee performance and attempts to coach underachievers using appropriate positive reinforcement.